Management accounting for decision makers - Atrill, Peter (Financial Times/Prentice Hall, 2006)
Designed to help you study, Management Accounting for Decision Makers is praised for its clear, accessible and uncluttered style. It provides a comprehensive introduction to the main principles of management accounting, with a strong practical emphasis and avoiding excessive technical detail. It has a clear and unequivocal focus on how accounting information can be used to improve the quality of decision making by managers, providing the perfect grounding for the decision makers of the future